Circular Economy Practices in Lombok Tourism Villages - Lale Yaqutunnafis; Reni Anggriani (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study examines the gap between tourism development and community welfare in West Lombok and develops a Human-Centered Circular Tourism Framework (HCCTF) based on local community perspectives. The research employs a participatory ethnographic approach using participant observation, in-depth interviews, and document analysis, with data triangulation to strengthen the validity of the findings. The results indicate that circular economy practices are deeply embedded in Sasak local wisdom and have been sustained across generations. Local communities respond to the limitations of linear tourism through alternative practices that integrate traditional values with innovation. The study also reveals tensions between dominant tourism narratives and the lived experiences of communities involved in tourism activities, creating challenges for meaningful participation and local empowerment. These findings suggest that sustainable tourism development should be rooted in local knowledge, cultural values, and community aspirations. Accordingly, the study proposes a Human-Centered Circular Tourism Framework that highlights the role of local wisdom in fostering more inclusive, equitable, and sustainable tourism development.